PENGARUH WAKTU PEMBAHARUAN SADAPAN POHON PINUS (Pinus merkusii) PADA UMUR BERBEDA TERHADAP PRODUKTIVITAS GETAH - Muhamad Ramdan; Raizal Fahmi Solihat; Asep Purwanto (Wanamukti: Jurnal Penelitian Kehutanan, 2020)
Pine sap exploitation is growing because demand for pine sap in Indonesia and the world is increasing. Pine sap productivity is influenced by several factors including tapping, tree species, diameter, and age of stands. In the tapping method, one of them is the renewal time of tapping with the quarre system which is supposed to save the tapping area and get the maximum sap. This paper studies the effect of the renewal of the pine tree tapping at different ages on the productivity of the sap. The proposed method is a survey with a purposive sample determination with 3 different treatments, namely treatment A of the 3-day quarre renewal, treatment B of the 5-day quarre renewal, and treatment of the renewal of the 7-day quarre by administering stimulants. Performed at different age classes IV, VI, and VIII. Field observational data is then processed using a factorial Completely Randomized Plan analysis with two factors. The results showed that the renewal of quarre had a significant effect on the average productivity of pine tree sap at 95% confidence intervals (α = 0.05). The highest average productivity on treatment B renewal of 5 days quarre was 12.17 grams /quarre/day at age classes VI and the lowest average productivity was at treatment C of renewal of 7 days with 4.61 grams /quarre/day at age classes IV.